2009
DOI: 10.1016/j.otohns.2009.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon radiation exposure in ESS with balloon catheters

Abstract: A recent publication reported low levels of surgeon radiation exposure during ESS with balloon catheters. This study validates radiation exposure among experienced surgeons is well below the annual occupational radiation exposure limit of 50,000 mrem. With vigilant technique and education, fluoroscopy reliance can be minimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(29 reference statements)
0
4
0
2
Order By: Relevance
“…[8][9][10] Costs and theatre time were also increased, with the need for additional equipment and a radiographer. This imaging procedure exposed the patient's (highly radiosensitive) lens and thyroid, and also the surgeon, to ionising radiation, although analysis of radiation doses has suggested that the dose is well within safe limits.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] Costs and theatre time were also increased, with the need for additional equipment and a radiographer. This imaging procedure exposed the patient's (highly radiosensitive) lens and thyroid, and also the surgeon, to ionising radiation, although analysis of radiation doses has suggested that the dose is well within safe limits.…”
Section: Methodsmentioning
confidence: 99%
“…Dentro de las controversias que genera su uso, destacan sus limitadas indicaciones, costos actuales elevados, la ausencia de remoción de tejido y los riesgos de la exposición a radiación 10,15,17 . Actualmente esto último se ha solucionado con la técnica de transiluminación.…”
Section: Tabla 2 Resultadosunclassified
“…La guía de transiluminación actualmente ha reemplazado al control fluoroscópico, evitando el riesgo de exposición a radiación descrito con anterioridad 10,14,15 . Se describe un patrón clásico de transiluminación del seno frontal, el que es medial, para evitar su mal posición en una celdilla supraorbitaria y eventuales complicaciones orbitarias 16 …”
Section: Procedimientounclassified
“…Reflections on radioprotection during ballooning procedures are no longer valid due to the introduction of the LUMA technique [ 1078 ], [ 1119 ] and navigated guide wires. Nevertheless, the measured irradiation exposition is very low for the patients (eye, total dose) and the ENT surgeon (hand, total dose, breast) and it is significantly below the critical threshold dose or the natural radiation exposure, however, it must be observed nonetheless [ 1119 ], [ 1120 ], [ 1121 ], [ 1122 ]. New developments concern a flexible tip, multifunctional dilatation products (probe, rinsing, and ballooning) [ 1123 ], the additional application of rinsing systems [ 1124 ], and navigable guiding catheters [ 1125 ] or guide wires.…”
Section: Technical Equipmentmentioning
confidence: 99%